KOMPETENSI GURU MATEMATIKA PEMULA DALAM MEMBUAT PERANGKAT PEMBELAJARAN SMP/MTs DI LOMBOK TIMUR - AMINULLAH AMINULLAH; KUSMIANTI KUSMIANTI (Universitas Mahasaraswati Mataram, 2018)
Teachers must be able to make and develop learning plans, create student activity sheets according to learning needs, and valid learning outcomes test. This study aims to describe the competence of beginner math teachers in making learning tools for SMP / MTs in East Lombok. This research is a survey research with descriptive statistical design that uses concurrent embedded strategy of mixed method approach. The number of samples in this study is 246 mathematics teachers who teach in SMP / MTs in East Lombok region, which are determined using purposive sampling technique. The research data is collected using instruments in the form of checklists and questionnaires. Data analysis uses quantitative descriptive statistical analysis with competency tendencies in five categories: very competent, competent, quite competent, less competent, and incompetent.The results obtained are 1) the beginner's mathematics teacher competence in making lesson plans is categorized as competent with a percentage of 60.98%, an average value of 81.287 and a standard deviation of 7.983. 2) Competence of beginner mathematics teachers in making LKS included in the category of quite competent with a percentage of 54.07%, an average value of 76.659 and a standard deviation of 7.739. 3) Competence of beginner math teachers in making THB included in the competent category with a percentage of 74.39%, an average value of 81.664 and a standard deviation of 7.135.